The particle size effect on the collision processes in complex plasma - Bastykova Н.Х.; Kodanova С.К.; Ramazanov Т.С.; Kosymbekov О.Д. (Recent Contributions to Physics, 2025)
The collision processes between ion with dust particle have been investigated on the basis of the modified Yukawa potential considering the dust particle size. The scattering as well as the capturing of ion in the field of the charged dust particle with different radius are considered. The scattering and collection cross sections are obtained in a wide range of the coupling parameter. The orbital and collection parts of ion drag force are obtained for different dust particle radius. Accounting the dust particle radius led to a sufficient change for both the momentum transfer cross section and the ion drag force. As it is found out, taking into account the size of dust particles leads to a reduction of the force due to scattering ions and on the reverse increases the force due to absorbing ions. The results of this work can be useful in the study of wave processes, formation of voids and other collective processes.